2022
DOI: 10.3389/fnhum.2022.919002
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant effect of cognitive reappraisal training on individuals cognitively vulnerable to depression: Could cognitive bias be modified through the prefrontal–amygdala circuits?

Abstract: Cognitive reappraisal (CR) is one of the core treatment components of cognitive behavioral therapy (CBT) and is the gold standard treatment for major depressive disorders. Accumulating evidence indicates that cognitive reappraisal could function as a protective factor of cognitive vulnerability to depression. However, the neural mechanism by which CR training reduces cognitive vulnerability to depression is unclear. There is ample evidence that the prefrontal–amygdala circuit is involved in CR. This study prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Other studies, on the other hand, have found that habitual suppression of thoughts and emotions may contribute to depression and anxiety disorders, whereas reappraisal was associated with less depression, less negative affect, and increased life satisfaction ( 90 92 ). Moreover, promising theoretical and practical evidence for the early intervention of depressed or anxious individuals and preventing or relieving stress-related difficulties was discovered in these studies when evaluating the effects of emotional regulation strategies on anxiety, depression, or other pathologies by training patients in CR or even positive reappraisal ( 91 101 ). In light of these effects, a moderation study was conducted to investigate the potential modulating effect of these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, on the other hand, have found that habitual suppression of thoughts and emotions may contribute to depression and anxiety disorders, whereas reappraisal was associated with less depression, less negative affect, and increased life satisfaction ( 90 92 ). Moreover, promising theoretical and practical evidence for the early intervention of depressed or anxious individuals and preventing or relieving stress-related difficulties was discovered in these studies when evaluating the effects of emotional regulation strategies on anxiety, depression, or other pathologies by training patients in CR or even positive reappraisal ( 91 101 ). In light of these effects, a moderation study was conducted to investigate the potential modulating effect of these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This result is helpful to understand the pathological mechanism of gender emotional disorder and give some reference for improving the treatment of male and female patients with emotional disorders in clinical settings [ 41 ]. For example, careful selection of materials in exposure therapy may be needed because of women’s emotional susceptibility, and cognitive therapy for women patients may require longer clinical treatment time for their additional trials to complete extinction.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we focus on reappraisal capacity, given previous findings showing its ability to mediate the link between stress and depressive symptoms 10 , to modify physiological 11 13 and affective 14 16 responses to negative emotions. Further, reappraisal is a central component of cognitive behavioral therapy for depression 17 highlighting it’s hypothesized role in mental health disorders. In the current study, we therefore sought to examine the association between reappraisal capacity and symptoms of depression and anxiety in a well-powered sample.…”
Section: Introductionmentioning
confidence: 99%